Severe headache presenting as an early sign of retroperitoneal para aortic paraganglioma. (June 2021) - Guruchannabasavaiah, B.; Madabhavi, Irappa V.; Avinash, D.B.; Aravindan, R.; Devarabhavi, Praveen; Dakappa, Pradeepa H.
Abstract: Background: Paraganglioma is a rare type of neuroendocrine tumor with the ability to secrete neuropeptide and catecholamines in excess. Sympathetic hyperactivity, severe persistent headache and hypertension is the most common clinical presentation of paraganglioma similar to pheocromocytoma. Case report We reported a case of 19 year old girl with severe headache and hypertension, from past 6 month. On further imaging evaluation for the headache, the computed tomography of the abdomen plus pelvis was suggestive of left pre para aortic paraganglioma measuring of 3.4 cm in diameter. Surgical excision of mass was done. Histopathological examination of surgical specimen was consistent with the diagnosis of paraganglioma. Patient is on regular follow up without any subjective or objective evidence of the disease. Conclusion: Retroperitoneal paraganglioma may be one of the causes for commonly occurring symptomatic headache, which is benign in nature, but possibility of transformation of malignant paraganglioma can occur. The surgical excision of mass is the treatment of choice.